EFFECT OF BRAND TRUST AND CONSUMER-BRAND CONGRUENCE ON CONSUMERS’ INTERPRETATION OF BRAND PERSONALITY IN PURCHASE OF BRANDED APPARELS - Joseph, Minu Mary; Anand, D. (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to illuminate the effect of brand trust and user-image congruence as decisive factors affecting brand personality while purchasing branded apparels. The relationship between Brand trust and Brand personality, the impact of consumer-brand congruence on brand personality attributes and the effect of brand personality on purchase intention towards branded apparel, are empirically tested. The findings from the consumers’ perspective suggest that brand trust and consumer-brand congruence have a significant impact on brand personality. It is also proved that brand personality as interpreted by consumer is a predominant determinant of purchase intention.